Pemanfaatan Lingkungan Untuk Pembelajaran Menulis Puisi Anak Berorientasi Karakter dengan Menggunakan Multisensori Siswa Sekolah Dasar - Vindi Avianti Wahyuning Setyowati (Jurnal Pendidikan Indonesia (JOUPI), 2023)
This article focuses on the use of the environment for learning to write poetry in children with character orientation using student multisensory. The aims of this article are (1) to find out the role of the environment in improving learning to write poetry for children with a character orientation (2) to improve poetry writing skills by applying students' multisensory abilities in elementary schools. The method used is descriptive qualitative research. The data collection technique used is a literature study. Data validation was carried out by triangulating data sources. The results of the study are (1) the role of the environment in improving poetry learning with character orientation in children (2) an increase in poetry writing skills by applying multisensory abilities. This research needs to be considered in order to improve students' ability to write a poem that contains moral values according to the age of the children and to improve children's multisensory abilities through poetry writing activities.